VARIASI TRAY AERATOR DENGAN PENAMBAHAN MEDIA KAOLIN DAN KARBON AKTIF UNTUK MENURUNKAN (Fe) DAN (Mn) TERLARUT DI AIR SUMUR - Hamsah Karuniawan; Munawar Ali (EnviroUS, 2021)
Ground Water as an alternative to clean water is often found to contain iron (Fe) and (Mn). The content of Fe and Mn causes a yellow-brown color and leaves a yellow stain on the fabric. Fe content can cause health problems such as nausea when consumed, intestinal wall damage and irritation to the eyes and skin. Meanwhile, Mn content above the quality standard can cause disturbances in the vascular vessels, heart and nervous system. This well water can be treated in several ways, one of which is aeration. Aeration is the process of adding air to water through contact between water and air. There are several types of aerators, one of which is the Tray aerator. The Tray aerator is aerated with a vertical Tray arrangement. The water will pass through the perforated Tray level and will be caught at the bottom. To increase the efficiency of reducing Fe and Mn levels, it can be done by adding Kaolin media and activated carbon. The effect of aeration time is directly proportional to the decrease in Fe and Mn levels. The longer the aeration time, the more significant the decrease in Fe and Mn levels. the contact time between water and gas becomes longer. As a result, the transfer of oxygen from the gas phase to the liquid phase can be maximized. The results of this study indicate that the addition of adsorbent media in Tray aerator variations affects the percent removal of Fe and Mn levels in well water. With the highest percentage removal of Fe was 86.09% with a result of 0.64 mg / l using 500 gr kaolin media for 90 minutes and the highest percentage of Mn removal was 88.70% with a yield of 0.26 mg / l in 90 minute